Ekonomi Aset Digital: Analisis Sentimen Masyarakat Berbasis Leksikon Terhadap Kebijakan Kripto di Indonesia - Hasyyati, Zata; Qausar, Haves; Yumni, Hazhiyah; Jannah, Miftahul (TIN: Terapan Informatika Nusantara, 2025)
This study analyzes the shift in public sentiment toward cryptocurrency regulation in Indonesia following policy implementation and identifies the role of cognitive biases in shaping public responses. The primary contribution of this research lies in the development of an integrative analytical framework that connects real-time social media data from X (formerly Twitter) with behavioral economics theory, alongside the formulation of evidence-based strategic recommendations. By applying text mining and lexicon-based sentiment analysis (InSet Lexicon), the study examines sentiment dynamics across two periods: pre-regulation (2009–2018), dominated by neutral sentiment (81.7%), and post-regulation (2019–2024), which exhibits a significant increase in negative sentiment (64.8%) alongside a fivefold growth in positive sentiment (31.7%). The findings reveal that cognitive mechanisms, such as loss aversion and status quo bias, amplify public resistance to new regulations. Policy implications include three innovative strategies: (1) redesigning communication using loss-avoidance framing, (2) enhancing financial literacy among younger generations, and (3) developing a more participatory regulatory sandbox. This study underscores the importance of adopting regulatory approaches that are responsive to public psychological dynamics and the prevailing low levels of financial literacy.